2016
DOI: 10.1016/j.str.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the ERp44-Peroxiredoxin 4 Complex Reveals the Molecular Mechanisms of Thiol-Mediated Protein Retention

Abstract: ERp44 controls the localization and transport of diverse proteins in the early secretory pathway. The mechanisms that allow client recognition and the source of the oxidative power for forming intermolecular disulfides are as yet unknown. Here we present the structure of ERp44 bound to a client, peroxiredoxin 4. Our data reveal that ERp44 binds the oxidized form of peroxiredoxin 4 via thiol-disulfide interchange reactions. The structure explains the redox-dependent recognition and characterizes the essential n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 46 publications
1
33
0
Order By: Relevance
“…During the evaluation process of this paper, Yang et al reported the crystal structure of the ERp44-Prx4 complex (32), which overall supports our proposed model of ERp44 binding to the client proteins. The observation that ERp44 prefers the oxidized form of Prx4 to its reduced form (32) can be explained by the different electrostatic surface properties between these two redox states.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…During the evaluation process of this paper, Yang et al reported the crystal structure of the ERp44-Prx4 complex (32), which overall supports our proposed model of ERp44 binding to the client proteins. The observation that ERp44 prefers the oxidized form of Prx4 to its reduced form (32) can be explained by the different electrostatic surface properties between these two redox states.…”
Section: Discussionsupporting
confidence: 80%
“…The crystal structure of the ERp44-Prx4 complex (32) reveals that a Cys29 (ERp44)-Cys208 (Prx4) intermolecular disulfide bond and a number of hydrogen bonds form at the interface between the ERp44 a domain and the Prx4 homodimer. In this context, the flexible C-terminal region of Prx4 assumes a β-strand, which forms hydrogen bonds with the β4-strand of ERp44 (32). Taken together, these observations suggest the following general mechanism of ERp44-client complex formation.…”
Section: Discussionmentioning
confidence: 99%
“…The mutation of Ero1α S145E was created using the Fast Mutagenesis System (TransGen). The expression of pcDNA3.1‐Ero1α‐myc, pcDNA3.1‐Ero1α‐HA, and/or pcDNA3.1‐HA‐ERp44 in mammalian cells was as previously described (Wang et al , ; Yang et al , ). pcDNA3.1‐Ero1α‐HA‐KDEL was generated by insertion of a KDEL motif between HA and the termination codon.…”
Section: Methodsmentioning
confidence: 99%
“…The complex structure of the Am Prx homolog and Am Trx homolog has been reported, which allowed us to build a structural model of the Am Prx‐ Am Trx complex. The structure of Am Trx modeled by the SWISS‐MODEL server (https://www.swissmodel.expasy.org/) was docked to a C terminus‐modified Am Prx dimer according to the interaction in human Prx4‐Erp44 complex (PDB entry http://www.rcsb.org/pdb/search/structidSearch.do?structureId=5HQP) . In this model, the α4‐β6 loop did not contact Am Trx, but it was located ~ 20 Å away from the Am Trx binding site (Fig.…”
Section: Resultsmentioning
confidence: 99%